L’expression de la modalité par des adjectifs : une comparaison entre l’adjectif grec ancien en -ιμος et l’adjectif latin en -bilis (ACME, 2020)
In this contribution a comparison is proposed between the Ancient Greek denominal adjective in -ιμος and the Latin deverbal adjective in -bilis from the point of view of their modal semantics. Despite the different nature of the derivational base – the adjectives in -ιμος are usually derived from action nouns while the adjectives in -bilis are derived from verbal bases –, both formations can convey a modal value of dynamic possibility or deontic necessity alongside other possible modal values. After presenting the most recent theoretical framework of reference for the interpretation of the semantic category of modality, the issue of the emergence of the modal value in diachrony as well as some related questions (such as whether and in what terms this value is inherent in the two suffixes) are addressed. Then, a systematization is attempted of the possible modal (or non-modal) values in relation to the nature of the derivational base, of the syntactic context and of the referent of the adjective. It is also proposed to distinguish between a morphological use (with the scope within the formation) and a lexical use (with the scope outside the formation) of the adjectives in -ιμος and in -bilis that has repercussions also at the level of the modal senses: only the lexical use seems to allow the deontic-evaluative and epistemic readings. This study has opened some new perspectives and, if comparison between the two formations is possible, the adjectives in -bilis present a much richer semantics than that of the adjectives in -ιμος. This difference, which remains to be examined in depth, can be explained, perhaps, by the closer link between the formations in -bilis and the formal class of the verb, while the formations in -ιμος derive mainly from the narrower class of action nouns.